2019
DOI: 10.1177/1934578x19843011
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl Acetate Extracts of Two Artemisia Species: Analyses of Phenolic Profile and Anticancer Activities Against SW-480 Colon Cancer Cells

Abstract: Because Artemisia vulgaris L. and Artemisia alba Turra are traditional medicinal plants used for the treatment of different diseases, we evaluated the cytotoxic/apoptotic activity of ethyl acetate extracts from these natural products against human colon cancer cells SW-480. The extracts contained a large amount of the total polyphenols and flavonoids. The phenolic profile showed the presence of phenolic acids (gallic, p-coumaric, vanillic, and ferulic acids) and flavonoids (rutin, myricetin, luteolin, querceti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Study on ethyl acetate extract of A. vulgaris L. and A. alba Turra showed that antiproliferative activities increased with time exposure. Both extracts contained phenolic compounds and flavonoids (Jakovljević et al 2019). The dichloromethane fraction of ethanol eluate of A. sacrorum Ledeb showed the most vigorous cytotoxic activities on HepG2, 49.76 and 28.51 µg/mL, respectively.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Study on ethyl acetate extract of A. vulgaris L. and A. alba Turra showed that antiproliferative activities increased with time exposure. Both extracts contained phenolic compounds and flavonoids (Jakovljević et al 2019). The dichloromethane fraction of ethanol eluate of A. sacrorum Ledeb showed the most vigorous cytotoxic activities on HepG2, 49.76 and 28.51 µg/mL, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…The three compounds may cause cytotoxic ability, but there are other compounds that we did not measure in this study. Jakovljević et al (2019) reported that an ethyl acetate extract of A. vulgaris and A. alba, which showed the antiproliferative activities, contained phenolic compounds that included phenolic acids (gallic, p-coumaric, vanillic, and ferulic acids), beside flavonoids included rutin, myricetin, luteolin, quercetin, and apigenin. Wang et al (2012) stated that there are various anticancer compounds, including kaempferol and triterpenoids.…”
Section: Discussionmentioning
confidence: 99%
“…For example, artemisinin, the most well-known antimalarial medicine, is derived from A. annua [6]. Many other phytochemicals, such as essential oils [7], flavonoids [8], terpenoids [8], phenolic acids [9], lignans [10], coumarins [10], organic acids [11], alkaloids [12], and tannins [13] are found in Artemisia species, which are thus a rich source of potentially medicinally or nutritionally beneficial bioactive compounds.…”
mentioning
confidence: 99%
“…For example,artemisinin, the most famous medicine used for antimalarial treatment, is derived from A.annua [5]. Except that, many other phytochemicals, such as essential oils [6], flavonoids [7], terpenoids [7], phenolic acids [8], lignans coumarins [9], organic acids [10], alkaloids [11], tannin [12], and other groups of metabolites were found in Artemisia species. Previous evidence showed that many ingredients have pharmacological activities including antioxidant [13][14], antiobesity [14], anti-inflammatory [14], antifungal [15], antibacterial [16], and anticoagulation [17] activities, etc.…”
mentioning
confidence: 99%